ANALYSIS OF LEADING COMMODITY OF AGRICULTURAL, FORESTRY, AND FISHING SUBSECTORS IN ACEH - Khalish Khairina; Angga Syahputra (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Growth Regional Domestic Product is an indicator to measure the success of economic condition. The 27,92 percent Aceh’s GRDP is contributed by agriculture, forestry, and fisheries sector, but this sector’s growth is decreased. This study aims to explore the leading subsector/commodity in agriculture, forestry, and fisheries sector. This study uses secondary data in the form of Aceh’s GRDP and Indonesia GDP from 2017-2021 taken from the Aceh BPS and Indonesia BPS Websites. Data is analyzed with three approaches namely Location Quotient, Dynamic Location Quotient and Differential Shift. It is found that the superior subsectors are horticultural crops, husbandry, and agricultural services & hunting with leading commodities namely large chilli, cayenne pepper, shallots, long beans, cucumber, bananas, papaya goats, broilers, free-range chickens, and ducks Furthermore, the sub-sector that has the potential to become a leading sector in the future is plantation crops. Although the competitiveness of the agricultural, forestry and fisheries sectors is still lower than the national level. However, this sector still plays a large role towards Aceh's GRDP.